Shrink Film

JP7629593B2Active Publication Date: 2025-02-14TOYO INK MFG CO LTD +2
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021135263
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-23
Publication Date
2025-02-14
Estimated Expiration
2041-08-23

AI Technical Summary

Benefits of technology

【0016】 本発明により、隠蔽性、熱収縮性を備え、表刷り印刷フィルムにおいても、密着性、耐熱性等の諸物性に加え、高い光沢性を発現できるシュリンクフィルムを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629593000001
    Figure 0007629593000001
  • Figure 0007629593000002
    Figure 0007629593000002
  • Figure 0007629593000003
    Figure 0007629593000003
Patent Text Reader

Abstract

To provide a shrink film which has concealability and thermal shrinkability, and can exhibit high glossiness in addition to various physical properties such as adhesion and heat resistance even in a surface printing film.SOLUTION: A shrink label contains an overcoat layer (A) containing a binder resin and an isocyanate curing agent, a printing layer (B), and a shrinkable base material (C). The binder resin of the overcoat layer (A) contains 30 mass% or more of a polyester-based resin in the whole binder resin, and the polyester-based resin contains 50 mass% or more of a constitutional unit derived from a dibasic acid and polyhydric alcohol in the whole polyester-based resin. Either or both of the binder resin and the isocyanate curing agent have at least one cyclic structure selected from an aromatic group, an alicyclic group, and a pyranose group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a shrink film comprising an overcoat layer, a printed layer, and a shrinkable substrate. [Background technology]

[0002] In recent years, it has been reported that plastic products such as bottles and packaging that have been discarded or dumped as garbage end up in the ocean, where they decompose over a long period of time into tiny fragments called microplastics. There is concern that when marine organisms ingest microplastics, harmful chemicals may accumulate in the human body through the food chain.

[0003] In the case of plastic bottles, polyester, polypropylene, and polyethylene are often used as the base material. These base materials are colored and printed from the viewpoints of protecting the contents, design, or providing product information, and are therefore not suitable for material recycling. For this reason, it has been proposed to color and print shrink film, rather than the bottle, and wrap it around the body of a transparent bottle as a shrink label (for example, Patent Document 1).

[0004] Printing on a film substrate is broadly divided into surface printing, in which printing is performed directly on the surface of the film, and reverse printing, in which ink is printed on the reverse side of the film. Surface-printed films can color the film substrate because a printing ink layer is formed on the outermost surface, but compared to the film substrate, they often have inferior glossiness, scratch resistance, and heat resistance (Patent Document 2). On the other hand, reverse-printed films have the characteristic that high glossiness and scratch resistance can be easily obtained compared to surface printing, in which the outermost layer is a printing layer, because the physical properties of the film substrate itself are effectively utilized. However, this method requires that after printing ink on the substrate, another film is pasted on the printing layer, which is a time-consuming process, and in addition, the physical properties due to the process, such as adhesion between the film substrate and the printing layer and delamination (floating), are often insufficient, and there is also a problem in terms of cost because adhesives and lamination processes are required. In addition, if the film substrate is not pasted, it is difficult to impart concealment to protect the contents.

[0005] Therefore, in order to impart high gloss and heat resistance to a surface-printed film, a method of forming a protective layer on the surface of the surface-printed layer using an overcoat agent has been investigated. This method is expected to impart gloss and scratch resistance to the same degree as a laminated body without going through a complicated manufacturing process as in the case of a laminated body. However, as conventional overcoat agents, urethane resin-based coating agents (Patent Document 3), acrylic resin-based coating agents (Patent Document 4), amide resin-based coating agents (Patent Document 5), polylactic acid-based overcoat agents (Patent Document 6), etc. have been proposed, but all of them have room for improvement in gloss and heat resistance, etc., compared to laminated bodies. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Utility Model Application Publication No. 56-167382 [Patent Document 2] JP 2019-119824 A [Patent Document 3] JP 2018-145283 A [Patent Document 4] Patent No. 5828196 [Patent Document 5] JP 2016-079306 A [Patent Document 6] JP 2003-147265 A Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention provides a shrink film that has hiding power and heat shrinkability, and that, even when used as a surface-printed film, is able to exhibit high gloss in addition to various physical properties such as adhesion and heat resistance. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to solve the above problems and have completed the present invention.

[0009] That is, the present invention provides a shrink film comprising an overcoat layer (A), a printed layer (B), and a shrinkable substrate (C), The overcoat layer (A) is formed from an overcoat agent containing a binder resin and an isocyanate curing agent, the binder resin contains a polyester-based resin in an amount of 30% by mass or more of the entire binder resin, and the polyester-based resin contains structural units derived from a polybasic acid and a polyhydric alcohol in an amount of 50% by mass or more of the entire polyester-based resin, A shrink film, characterized in that either or both of the binder resin and the isocyanate curing agent contain at least one cyclic structure selected from an aromatic ring, an alicyclic ring, and a heterocyclic ring.

[0010] The present invention also relates to the above shrink film, wherein the content of the cyclic structure is 7 to 50 mass % based on the total mass of the solid content of the overcoat agent.

[0011] The present invention also relates to the above shrink film, wherein the polyester resin has an ester bond concentration of 0.5 mmol / g to 12.0 mmol / g.

[0012] The present invention also relates to the above shrink film, wherein the isocyanate curing agent contains an adduct type isocyanate compound and / or a biuret type isocyanate compound.

[0013] The present invention also relates to the above shrink film, wherein the binder resin further contains a cellulose-based resin or a vinyl chloride copolymer resin, and the mass ratio of the polyester-based resin to the cellulose-based resin or the vinyl chloride copolymer resin is 90:10 to 30:70.

[0014] The present invention also relates to a shrink film according to any one of claims 1 to 5, wherein the printed layer (B) includes a layer in which either or both of a white layer and a black layer are solid printed.

[0015] The present invention also relates to the above shrink film, which has an average transmittance of 15% or less at 400 to 700 nm and a 60° gloss of 20 or more after the printing layer and overcoat layer are applied. Effect of the Invention

[0016] The present invention can provide a shrink film that has hiding power and heat shrinkability, and that can exhibit high gloss in addition to various physical properties such as adhesion and heat resistance, even when used as a surface-printed film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The following describes the embodiments of the present invention in detail. However, the following description of the embodiments or requirements is merely an example of how the present invention can be implemented, and the present invention is not limited to these details as long as it does not deviate from the gist of the present invention.

[0018] <Overcoat layer (A)> The present invention relates to a shrink film composed of an overcoat layer, a print layer, and a shrinkable substrate. The overcoat layer is formed from an overcoat agent, and the overcoat agent contains a binder resin containing a polyester resin and an isocyanate curing agent. The polyester resin in the overcoat agent imparts flexibility and adhesion, and the isocyanate curing agent imparts heat resistance and scratch resistance. In order to improve gloss and adhesion, the binder resin and / or the isocyanate curing agent have a cyclic structural group, and the cyclic structural group contains at least one selected from the group consisting of an aromatic group, an alicyclic group, and a heterocyclic group. The content of the cyclic structural group is preferably 7 to 50 mass% of the total mass of solids in the overcoat agent, more preferably 10 to 30 mass%, and even more preferably 15 to 40 mass%. The solid content refers to the total mass of non-volatile components of the overcoat agent.

[0019] (Content of Cyclic Structural Group) The content of the cyclic structural group can be calculated by the following formula. Content of cyclic structures (%) = Sum of atomic weights of atoms constituting cyclic structural groups in raw material / Sum of atomic weights of all atoms in raw material Here, the raw material refers to compounds constituting the overcoat agent, such as a binder resin or an isocyanate-based curing agent, and all atoms constituting the cyclic structure refer to carbon atoms or heteroatoms constituting the cyclic structure itself, such as an aromatic ring, an alicyclic ring, or a heterocyclic ring, and hydrogen atoms directly bonded to these atoms, and is defined as not including atoms of groups other than hydrogen atoms, such as methyl groups and nitro groups, which are substituted on or adjacent to the cyclic structure. For example, in the case of a xylylene diisocyanate trimethylolpropane adduct compound (XDI-TMP adduct, C36H35N6O9) which is an isocyanate curing agent, there are three aromatic ring structures (C6H4=76.1) with a total molecular weight of 695.7, and the total molecular weight of these is 228.3, so the ring structure content is 228.3 / 695.7=33%. The ring structure content in the total solid mass of the overcoat agent is obtained by multiplying the ring structure content of each molecule by the ratio of the molecule to the solid content of the overcoat agent.

[0020] The overcoat agent of the present invention is preferably used for surface printing. In the present invention, surface printing refers to a case where, when a shrinkable substrate is printed, the printing ink (printing layer) and the overcoat agent (overcoat layer) are printed on the substrate in that order, and the printed pattern can be confirmed from the printed surface, i.e., the overcoat layer side. In other words, the overcoat layer made of the overcoat agent becomes the outermost layer in the shrink film of the present invention. Hereinafter, each material constituting the overcoat agent of the present invention will be described.

[0021] <Binder resin> The binder resin refers to a resin that is the main component contained in the overcoat agent, and the total amount of the binder resin contains polyester resin at 30% by mass or more, and preferably at 50% by mass or more. The binder resin preferably has the above-mentioned cyclic structure, and the cyclic structure is selected from an aromatic ring (aromatic cyclic structure), an alicyclic ring (alicyclic cyclic structure), and a heterocyclic ring (pyranose cyclic structure, etc.). The cyclic structure is preferably contained in an amount of 5 to 60% by mass, and more preferably 20 to 50% by mass, of the total mass of the binder resin.

[0022] <Polyester resin> The polyester resin is not particularly limited as long as it contains 50% by mass or more of the structural units derived from polybasic acid and polyhydric alcohol in the total mass of the polyester resin, and is appropriately produced by a known method. The polyester resin preferably has at least one cyclic structure selected from aromatic ring, alicyclic ring, and heterocyclic ring as described above. The cyclic structure is preferably an aromatic ring and / or an alicyclic ring. The content of the cyclic structure in the polyester resin is preferably 1 to 80% by mass, more preferably 10 to 50% by mass. Examples of the polyester resin include polyester resins obtained by reacting polyhydric alcohol and carboxylic acid using a known esterification polymerization reaction, and alkyd resins described below. The polyester resin may further be modified with acrylic or isocyanate, and generally classified as an acrylic resin or a urethane resin, as long as it contains 50% by mass or more of the structural units derived from polybasic acid and polyhydric alcohol in the total mass of the polyester resin. The structural unit derived from a dibasic acid and a polyhydric alcohol refers to an integral structural unit in which a structural unit derived from a dibasic acid and a structural unit derived from a polyhydric alcohol are directly bonded to each other.

[0023] The weight average molecular weight of the polyester resin is preferably 500 to 100,000, and more preferably 2,000 to 50,000, because this improves adhesion and blocking resistance, as well as work efficiency and printability in the ink printing process.

[0024] Examples of alicyclic alcohols among polyhydric alcohols include 1,4-cyclohexanediol, 1,2-cyclohexanediol, 1,4-cyclohexanedimethanol, 1,2-cyclohexanedimethanol, spiroglycol, and isosorbide. In addition, monofunctional alcohols such as cyclohexanol, cyclohexaneethanol, 4-tert-butylcyclohexanol, menthol, 2-ethyl-4-(2,2,3-trimethyl-3-cyclopentenyl)-2-buten-1-ol, 4-isopropylcyclohexanol, and 2-(tert-butyl)cyclohexanol can also be used in combination. The polyhydric alcohols can be used alone or in a mixture of two or more kinds.

[0025] Among the polyhydric alcohols, examples of aromatic alcohols include 1,4-benzenedimethanol, 1,3-bis(2-hydroxyethoxy)benzene, 1,2-bis(2-hydroxyethoxy)benzene, 1,4-bis(2-hydroxyethoxy)benzene, hydroquinone, 2,2-bis(4-β-hydroxyethoxyphenyl)propane, and the like. These can be used alone or in combination of two or more.

[0026] Among the polybasic acids, examples of alicyclic dibasic acids include 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 1,1-cyclopentanediacetic acid, and decahydro-1,4-naphthalenedicarboxylic acid.

[0027] Among the polybasic acids, examples of aromatic polybasic acids include phthalic acid, isophthalic acid, terephthalic acid, 1,2-phenylene diacetic acid, 1,3-phenylene diacetic acid, 1,4-phenylene diacetic acid, 4-(carboxymethyl)benzoic acid, trimellitic acid, and pyromellitic acid, which may be used alone or in combination of two or more.

[0028] In addition, for the polyester resin, a polyhydric alcohol having no cyclic structure or a polybasic acid having no cyclic structure can also be used.

[0029] Examples of polyhydric alcohols not having an alicyclic structure include, but are not limited to, ethylene glycol, 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3-propanediol, 2-ethyl-2-butyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,2-pentanediol, 3-methyl-1,5-pentanediol, hexanediol, octanediol, 1,4-butynediol, 1,4-butylenediol, diethylene glycol, triethylene glycol, dipropylene glycol, glycerin, trimethylolpropane, trimethylolethane, 1,2,6-hexanetriol, 1,2,4-butanetriol, sorbitol, and pentaerythritol.

[0030] Examples of polybasic acids having no cyclic structure include, but are not limited to, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, phthalic acid, etc. If necessary, monobasic acids such as formic acid, acetic acid, propionic acid, butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, hexanoic acid, octanoic acid, nonanoic acid, decanoic acid, oleic acid, and linoleic acid may be used in combination.

[0031] Furthermore, acid anhydrides may be used, such as succinic anhydride, methyl succinic anhydride, 2,2-dimethyl succinic anhydride, butyl succinic anhydride, isobutyl succinic anhydride, hexyl succinic anhydride, octyl succinic anhydride, dodecenyl succinic anhydride, phenyl succinic anhydride, glutaric anhydride, 3-allyl glutaric anhydride, 2,4-dimethyl glutaric anhydride, 2,4-diethyl glutaric anhydride, butyl glutaric anhydride, and hexyl glutaric anhydride. Acid, Maleic Anhydride, 2-Methyl Maleic Anhydride, 2,3-Dimethyl Maleic Anhydride, Butyl Maleic Anhydride, Pentyl Maleic Anhydride, Hexyl Maleic Anhydride, Octyl Maleic Anhydride, Decyl Maleic Anhydride, Dodecyl Maleic Anhydride, 2,3-Dichloro Maleic Anhydride, Phenyl Maleic Anhydride, 2,3-Diphenyl Maleic Anhydride, Itaconic Anhydride, Citraconic Anhydride, Phthalic Anhydride, 4-Methyl Phthalic Anhydride, Dimer Acid, 1,2,3,6-Tetrahydrophthalic Anhydride, 3-Methyl-1,2,3,6-Tetrahydrophthalic Anhydride, 4-Methyl-1,2,3,6-Tetrahydrophthalic Anhydride, 3-Methyl-1,2,3,6-Tetrahydrophthalic Anhydride, 4-Methyl-1,2,3,6-Tetrahydrophthalic Anhydride, Methylbutenyl-1,2,3,6-Tetrahydrophthalic Anhydride, Chlorendic Anhydride, Head Acid Anhydride, Biphenyldicarboxylic Anhydride, Himic Anhydride Examples of suitable anhydrides include phthalic anhydride, endomethylene-1,2,3,6-tetrahydrophthalic anhydride, methyl-3,6-endomethylene-1,2,3,6-tetrahydrophthalic anhydride, 1-cyclopentene-1,2-dicarboxylic anhydride, methylcyclohexene dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, 1,8-naphthalenedicarboxylic anhydride, and octahydro-1,3-dioxo-4,5-isobenzofurandicarboxylic anhydride.

[0032] (Alkyd resin) Examples of alkyd resins include alkyd resins synthesized by polycondensation of carboxylic acid compounds and fatty acids (or animal and vegetable oils) with alcohol compounds, and alkyd resins obtained by reacting animal and vegetable oils or their fatty acid monoesters with carboxylic acid compounds, followed by esterification of alcohol compounds. All of these are alkyd resins modified from fats and oils. The alkyd resin used in the present invention has a hydroxyl value of preferably 5 to 200 mgKOH / g, more preferably 20 to 150 mgKOH / g. The weight average molecular weight of the alkyd resin is preferably 500 to 100,000, more preferably 2,000 to 50,000. The content of the cyclic structure in the alkyd resin is preferably 1 to 80 mass%, more preferably 10 to 50 mass%.

[0033] The carboxylic acid compound used in the alkyd resin is preferably a polybasic acid such as a dibasic acid. Examples of the dibasic acid include the aromatic carboxylic acids (including anhydrides), alicyclic carboxylic acids, and the like. Among them, aromatic carboxylic acids (including anhydrides) are preferred. It is preferable that the compound is phthalic anhydride, phthalic acid, isophthalic acid, terephthalic acid, Among these, carboxylic acid and the like are preferred.

[0034] The above-mentioned alcohol compounds used in the alkyd resin are preferably alicyclic alcohols, aromatic alcohols, and alcohols that do not have a cyclic structure, and the same as above can be preferably used.Among them, it is preferable to use alcohols that do not have a cyclic structure, and as dihydric alcohol compounds, ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, butanediol, 1,6-hexanediol, 1,2-hexanediol, 1,5-hexanediol, 2,5-hexanediol, cyclohexanedimethanol, nepentyl glycol, etc. are preferably exemplified, and as trihydric or higher alcohol compounds, aliphatic polyhydric alcohols such as (mono- or di- or tri-)glycerin, (mono- or di- or tri-)trimethylolethane, (mono- or di- or tri-)trimethylolpropane, (mono- or di- or tri-)trimethylolalkane, (mono- or di- or tri-)pentaerythritol, sorbitol, etc. are exemplified.

[0035] Examples of the animal and vegetable oils include hemp seed oil, linseed oil, perilla oil, oiticica oil, olive oil, cacao oil, kapok oil, kaya oil, mustard oil, apricot kernel oil, tung oil, kukui oil, walnut oil, poppy oil, sesame oil, safflower oil, radish seed oil, soybean oil, radish seed oil, camellia oil, corn oil, rapeseed oil, niger oil, rice bran oil, palm oil, castor oil, sunflower oil, grape seed oil, almond oil, pine seed oil, cottonseed oil, coconut oil, peanut oil, and dehydrated castor oil.

[0036] The fatty acid may be a mixed fatty acid, and suitable examples of the fatty acid include caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, oleic acid, linoleic acid, linolenic acid, palmitic acid, and stearic acid.

[0037] The fatty acid monoester may be an alkyl ester formed from the fatty acid and an alcohol, and suitable examples of the alcohol include alkanols such as methanol, ethanol, propanol, isopropanol, butanol, and isobutanol.

[0038] (Ester bond concentration) In an embodiment of the present invention, the polyester resin preferably has an ester bond concentration of 0.5 mmol / g to 12.0 mmol / g, and more preferably 4.0 mmol / g to 10.5 mmol / g. This is because the adhesion, blocking resistance, solubility in organic solvents, etc. are improved. The ester bond concentration here is a numerical value calculated by the following formula (1). Formula (1) Ester bond concentration (mmol / g) = total number of moles of ester bonds in polyester resin (mmol) / total mass of solid content of polyester resin (g) As described above, the ester bond concentration represents the number of moles of ester bonds relative to the total amount of polyester resin. For example, in the case of polyethylene terephthalate, the repeating unit formed by polycondensation of terephthalic acid and ethylene glycol has a molecular weight of 166 for terephthalic acid and 62 for ethylene glycol, and after subtracting dehydration, the repeating unit molecular weight is 192 (166 + 62 - 2 × 18 = 192), which contains 2 moles of ester bonds, so the ester bond density is calculated as 2 / 192 = 0.0104 mol / g = 10.4 mmol / g.

[0039] <Cellulose-based resin> In the overcoat agent of the present invention, it is preferable to use a cellulose-based resin in combination in order to improve gloss and heat resistance. Specifically, nitrocellulose, cellulose acetate propionate, cellulose acetate butyrate, hydroxyalkylcellulose, carboxyalkylcellulose, etc. are mentioned, and the alkyl group is, for example, a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a pentyl group, a hexyl group, etc., and the alkyl group may further have a substituent. Among them, cellulose acetate propionate, cellulose acetate butyrate, and nitrocellulose are preferable. As for the molecular weight, a weight average molecular weight of 5,000 to 300,000 is preferable, 10,000 to 200,000 is more preferable, and 10,000 to 100,000 is even more preferable. In addition, a glass transition temperature of 100°C to 160°C is preferable.

[0040] (nitrocellulose) Nitrocellulose is preferably obtained as a nitric acid ester by reacting natural cellulose with nitric acid to replace three hydroxyl groups in a six-membered ring of an anhydrous glucopyranose group in the natural cellulose with nitric acid groups, and the weight-average molecular weight is preferably in the same range as above. In addition, the average degree of polymerization is preferably in the range of 35 to 480, more preferably 50 to 200. When the average degree of polymerization is 50 or more, the strength of the ink film is improved, and the abrasion resistance and rubbing resistance are improved, which is preferable. When the average degree of polymerization is 200 or less, the solubility in solvents, the low-temperature stability of the ink, and the compatibility with the co-used resin are improved, which is preferable. In addition, the nitrogen content is preferably 10.5 to 12.5 mass%.

[0041] In one embodiment, the binder resin preferably contains the polyester resin and the cellulose resin. In this case, the ratio of the polyester resin to the cellulose resin is preferably 90:10 to 30:70 by mass, and more preferably 70:30 to 40:60 by mass. The polyester resin preferably contains an alkyd resin. The cellulose resin preferably contains nitrocellulose. The binder resin preferably contains 70% by mass or more of the polyester resin and the cellulose resin, and more preferably 80% by mass or more.

[0042] <Concomitant Resin> <Vinyl Chloride Copolymer Resin> In the embodiment of the present invention, the binder resin is also suitable for use in combination with other resins in addition to the above polyester-based resins and cellulose-based resins, and examples thereof include, but are not limited to, polyurethane resins, polyamide resins, vinyl chloride copolymer resins such as vinyl chloride-vinyl acetate copolymer resins and vinyl chloride-acrylic copolymer resins, rosin resins, ethylene-vinyl acetate copolymer resins, vinyl acetate resins, acrylic resins, styrene resins, dammar resins, styrene-maleic acid copolymer resins, styrene-acrylic copolymer resins, terpene resins, phenol-modified terpene resins, ketone resins, cyclized rubbers, chlorinated rubbers, butyral, polyacetal resins, petroleum resins, and modified resins thereof. These resins can be used alone or in combination of two or more.

[0043] <Isocyanate hardener> In the overcoat agent of the present invention, an isocyanate curing agent is used to improve heat resistance. In order to improve gloss, it is preferable that the isocyanate curing agent has a cyclic structure. Specifically, polyisocyanate compounds and modified isocyanate compounds can be suitably used as the isocyanate curing agent. Specifically, the modified isocyanate compound is preferably a dimeric allophanate type isocyanate compound, a trimer biuret type isocyanate compound, an adduct type isocyanate compound, and an isocyanurate type isocyanate compound. The biuret type isocyanate compound is an isocyanate compound having a structure in which urea is dimerized. In addition, the isocyanurate type isocyanate compound refers to an isocyanate compound that is a cyclic trimer of a polyisocyanate compound. The adduct type isocyanate compound refers to an adduct of a polyisocyanate compound and a polyhydric alcohol, and examples thereof include a reaction product of xylylene diisocyanate and trimethylolpropane. As the polyisocyanate compound, diisocyanates are preferred, and aromatic diisocyanates such as xylylene diisocyanate, diphenylmethane diisocyanate, tolylene diisocyanate, etc., alicyclic diisocyanates such as 1,4-cyclohexane diisocyanate, isophorone diisocyanate, etc., aliphatic diisocyanates such as hexamethylene diisocyanate, etc., and aromatic aliphatic diisocyanates such as α,α,α',α'-tetramethylxylylene diisocyanate, etc. are suitable. Specific examples of commercially available modified isocyanate compounds include Duranate 24A-100, 22A-75P, TPA-100, TKA-100, and P301-75E (manufactured by Asahi Kasei Corporation), Takenate D-160N, D-170N, D-110N, and D-101 (manufactured by Mitsui Chemicals), Desmodur N3200, N3600, Z4470BA, and L75(C) (manufactured by Covestro). The isocyanate curing agent preferably contains 5 to 50% by mass of a cyclic structure, and more preferably contains 20 to 40% by mass. The cyclic structure preferably has an alicyclic group and / or an aromatic group.The isocyanate curing agent preferably has an isocyanate group (NCO) content, as defined in JIS K6806, of 3 to 30% (mass %), and more preferably 5 to 25%.

[0044] The isocyanate curing agent is preferably mixed in an amount of 0.2 to 8 equivalents per equivalent of the crosslinkable functional group (such as a hydroxyl group or an amino group) of the binder resin, more preferably 0.8 to 3 equivalents. The ratio of the binder resin to the isocyanate curing agent used is preferably 95:5 to 10:90 by mass, and even more preferably 90:10 to 20:80 by mass. Within this range, sufficient crosslink density is obtained, and heat resistance is good. After applying the overcoat agent, aging is preferably performed to enhance reactivity. Here, aging refers to storage at a constant temperature and humidity for several hours to several days. The aging may be performed under the conditions of a normal isocyanate curing agent, for example, 1 to 10 days at room temperature, or 1 to 3 days at 40°C.

[0045] <Additives> The overcoat agent used in the present invention may appropriately contain additives that are conventionally known. In producing the overcoat agent, additives such as a wetting agent, an adhesion aid, a leveling agent, an antifoaming agent, an antistatic agent, a viscosity modifier, a chelating crosslinking agent, a trapping agent, an antiblocking agent, a wax component other than those mentioned above, and a silane coupling agent may be used as necessary.

[0046] <Organic solvent> The overcoat agent of the present invention preferably contains an organic solvent as a liquid medium (organic solvent-based overcoat agent). Although not limited to the following, the organic solvent used may be a known organic solvent such as an aromatic organic solvent such as toluene or xylene, a ketone-based organic solvent such as methyl ethyl ketone or methyl isobutyl ketone, ethyl acetate, n-propyl acetate, isopropyl acetate, isobutyl acetate, an ester-based organic solvent, an alcohol-based organic solvent such as methanol, ethanol, n-propanol, isopropanol, or n-butanol, or a glycol ether-based solvent such as ethylene glycol monopropyl ether or propylene glycol monomethyl ether, or may be used in combination. Among them, an organic solvent that does not contain an aromatic organic solvent such as toluene or xylene (non-toluene-based organic solvent) is more preferable. More preferably, an organic solvent consisting of an ester-based organic solvent or an alcohol-based organic solvent is preferable. In this case, the glycol ether-based organic solvent may be contained in an amount of 6% by mass or less in 100% by mass of the overcoat agent. The overcoat agent of the present invention may contain water as a liquid medium, but the content of water is preferably 0.1 to 5% by mass in 100% by mass of the liquid medium. However, it is not limited to these.

[0047] (Manufacturing of overcoat agents) The overcoat agent is produced by, without any particular limitation, mixing and stirring the binder resin solution, in which the binder resin and the organic solvent are dissolved or dispersed, and the solvent in a stirrer equipped with stirring blades, rotors, etc. There is no particular limitation on the stirring speed, and stirring can be performed at 50 to 300 rpm. In order to improve the handling and application properties of the overcoat agent, further solvent can be added as appropriate. The isocyanate curing agent can be charged at the beginning, but depending on the storage conditions and the type of isocyanate curing agent, it is preferable to mix it just before use. Since the overcoat agent is used by printing methods, etc., it is preferable that the viscosity is 20 to 200 mPa·s.

[0048] (Overcoat application and printing) The overcoat agent of the present invention is applied onto a printed layer formed by printing ink to form a shrink film. The overcoat agent of the present invention can be applied by a known printing method. For example, gravure printing, flexographic printing, microgravure printing, etc. can be mentioned, and gravure printing is preferred. In the gravure printing method, the overcoat agent enters the recesses that become the image areas engraved on the surface of a cylindrical cylinder, and after the overcoat agent of the non-image areas is scraped off with a metal plate called a doctor, the overcoat agent remaining in the recesses of the cylinder is transferred onto the printing film to form a coating layer. The amount of overcoat agent applied can be controlled by the depth of the recesses. The coating on the printing film can be applied multiple times, taking into consideration the film properties such as drying after coating, gloss of the coating film, scratch resistance, and high-temperature hot water resistance. The amount of coating and the number of coatings can be appropriately selected as the form of use of the overcoat agent. The thickness of the transparent protective layer formed by the overcoat agent of the present invention is preferably 0.5 to 10 μm, more preferably 1 to 6 μm.

[0049] The applied overcoat agent is preferably dried at a temperature of 40 to 80° C. The obtained overcoat layer is aged at room temperature to 40° C. for about 1 to 10 days as required to form a shrink film having an overcoat layer with a strong transparent protective function.

[0050] <Print layer (B)> The print layer is formed from printing ink. The printing ink is preferably a printing ink consisting of a binder resin, a pigment, a solvent, and, if necessary, an additive. Although not limited to the following, the printing ink is preferably a printing ink containing, as the binder resin constituting the printing ink, a urethane resin, a polyamide resin, an acrylic resin, a vinyl chloride-vinyl acetate copolymer resin, a nitrocellulose resin, a chlorinated polypropylene resin, an ethylene-vinyl acetate copolymer resin, a vinyl acetate resin, a polyester resin, an alkyd resin, a rosin-based resin, a rosin-modified maleic acid resin, a ketone resin, a cyclized rubber, a chlorinated rubber, butyral, a petroleum resin, or the like. Among them, it is more preferable that the printing ink contains at least one selected from the group consisting of a urethane resin, a polyamide resin, an acrylic resin, a vinyl chloride-vinyl acetate copolymer resin, and a nitrocellulose resin. In particular, a printing ink containing a urethane resin is more preferable because it has good adhesion to a film substrate.

[0051] The urethane resin can be obtained by a known method, for example, the method disclosed in JP-A-62-153366, JP-A-62-153367, JP-A-1-236289, JP-A-2-64173, JP-A-2-64174, JP-A-2-64175, etc. Specifically, it is produced by a two-stage method in which a polyol and a diisocyanate compound are reacted in a ratio in which the isocyanate group is in excess to obtain a prepolymer having an isocyanate group at the end, and the obtained prepolymer is reacted with a chain extender and / or a reaction terminator in a suitable solvent, or a one-stage method in which a polyol, a diisocyanate compound, a chain extender and / or a reaction terminator are reacted at once in a solvent. Among these methods, the two-stage method is preferable to obtain a uniform urethane resin.

[0052] In the present invention, at least one of the white layer and the black layer, or both of the layers are solid printed, thereby contributing to the hiding power. The printing ink used for the white layer is composed of at least coloring material, additives, and organic solvents, and contains 50% or more by weight of white pigment relative to the total coloring material. It does not have to look pure white. The black layer is made by blending at least a coloring material, an additive, and an organic solvent. By blending a black pigment, high concealing properties can be obtained even in small amounts. The black pigment is contained in an amount of more than 50% by weight based on the total coloring material. The appearance does not have to be black, and may be gray or the like. The print layer may have one or more chromatic layers containing chromatic colorants in addition to the white layer and / or the black layer. The amount of black pigment blended is not particularly limited as long as it does not affect the printing color of the chromatic color layer, but in the white layer, the amount of black pigment is preferably 1% by mass or less per 100% by mass of white pigment. In the present invention, the "shrink film" having a printed layer is also referred to as a "printed matter".

[0053] The printing ink may contain additives, such as pigment dispersants, leveling agents, defoamers, leveling agents, waxes, trapping agents, plasticizers, infrared absorbers, ultraviolet absorbers, anti-blocking agents, antistatic agents, and flame retardants.

[0054] The printing ink contains a coloring material, and as the coloring material, a pigment or a dye can be used. As the pigment, any of the CI pigments described in the Color Index that can be generally used in printing inks and paints can be used. For example, color pigments such as titanium oxide, red iron oxide, Prussian blue, ultramarine blue, carbon black, graphite, and extender pigments such as calcium carbonate, kaolin, clay, barium sulfate, aluminum hydroxide, and talc can be used. Furthermore, as the organic pigment, soluble azo pigments, insoluble azo pigments, azo chelate pigments, condensed azo pigments, copper phthalocyanine pigments, condensed polycyclic pigments, and the like can be used. The content of these pigments in the printing ink can be 0.5 to 50% by weight.

[0055] As the organic solvent used in the printing ink, the same solvent as that usable in the above-mentioned overcoat agent can be used, and known alcohol-based organic solvents, ketone-based organic solvents, ester-based organic solvents, aliphatic hydrocarbon-based organic solvents, and alicyclic hydrocarbon-based organic solvents can be used. Taking into consideration the solubility of the urethane resin and the co-resin, drying properties during printing, etc., it is preferable to use them in a mixed state.

[0056] The printing ink may contain a solvent, such as water or an organic solvent. The printing ink can be produced by a known method of dispersing a pigment using a resin, a solvent, etc. For example, the printing ink can be obtained by a method in which a pigment dispersion is produced by dispersing a pigment in a solvent using a urethane resin, a co-used resin, a dispersant, etc., and a resin, an additive, etc. are blended with the obtained pigment dispersion as necessary.

[0057] <Shrinkable base material (C)> The shrinkable substrate used in the present invention can be a plastic substrate in the form of a film. The plastic substrate can be a polyolefin substrate such as polyethylene and polypropylene, a polyester substrate such as polyethylene terephthalate, polylactic acid, or the like, a polystyrene substrate, a polystyrene-based resin such as AS resin or ABS resin, a polycarbonate substrate, a polyamide substrate, a polyvinyl chloride substrate, a polyvinylidene chloride substrate, or a film or sheet made of a composite material of these. Among them, a polyester-based resin or a styrene-based resin is preferred in that a uniform finish with less shrinkage unevenness and wrinkles can be obtained even if temperature unevenness occurs during the shrinkage process (heating process).

[0058] The above-mentioned plastic substrate may be (1) a single-type plastic substrate, or (2) a multi-layer plastic substrate in which multiple types of plastic substrates are multi-layered. In the present invention, a single-layer plastic substrate is preferred from the viewpoint of uniformity of shrinkage temperature and shrinkage rate.

[0059] When a plastic bottle is used as the shrinkable base material, if it is required to improve the concealing property in order to prevent deterioration of the contents, it is preferable to blend a light-absorbing substance such as titanium oxide so as to reduce the average transmittance in the range of 400 to 700 nm. It is preferable to mix titanium oxide having an average particle diameter of 0.15 to 0.35 μm in the shrinkable base material. By being in the range of 0.15 to 0.35 μm, a high reflection effect in the visible region is obtained, which contributes to hiding power. It is preferably 0.18 to 0.28 μm. The crystal form of titanium oxide can be rutile, anatase, or brookite, but rutile and anatase are preferable. The rutile type has a higher refractive index and higher reflection efficiency than other types, so that it can further increase hiding power. The average particle diameter is the average of particle diameters (for example, about 20 particles) that can be observed from a magnified image (for example, 1,000 to 10,000 times) of a scanning electron microscope. The particle shape of titanium oxide can be any known particle shape such as spherical, elliptical, rod-like, or fibrous. Here, for particles with an aspect ratio of 1.5 or more, the average of the major axis is taken as the average primary particle diameter.

[0060] Titanium oxide can have a coating layer formed of a metal oxide and / or an organic substance. The presence of such a coating layer suppresses deterioration of the resin due to catalytic activity and improves dispersion in the resin, so that high hiding power can be imparted even at a low concentration.

[0061] The metal oxide coating layer of titanium oxide is preferably an oxide of aluminum, silicon, or zirconium, and may be a hydrous oxide, such as hydrous alumina (Al2O3·nH2O), hydrous silica (SiO2·nH2O), or hydrous zirconium (ZrO2·nH2O).

[0062] The metal oxide coating layer of titanium oxide is preferably coated with 0.2 to 4 mass% of aluminum oxide based on 100 mass% of titanium dioxide before surface coating, and silicon oxide or zirconium oxide is preferably coated with 0.1 to 3 mass% of each based on 100 mass% of titanium dioxide before surface coating.

[0063] The organic coating layer contributes to the dispersion of titanium oxide, and examples thereof include polyhydric alcohols, organosilicon compounds, amines, amino acids, fatty acids, carboxylates, metal soaps, and waxes. Among these, polyhydric alcohols and organosilicon compounds are preferred. One or more organic substances can be used. The surface coating amount using the organic substance is preferably 0.1 to 3 wt % relative to 100 wt % of titanium dioxide before treatment, and more preferably 0.1 to 1.5 wt %.

[0064] Specific examples of polyhydric alcohols that can be used in the present invention include trimethylolethane, trimethylolpropane, ditrimethylolpropane, trimethylolpropane ethoxylate, and pentaerythritol, with trimethylolpropane and trimethylolethane being preferred.

[0065] Examples of the organosilicon compound that can be used in the present invention include organosilanes, organopolysiloxanes, and organosilazanes.Specific examples of organosilanes include aminopropyltriethoxysilane, N-β(aminoethyl)γ-aminopropyltriethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-(methacryloyloxypropyl)trimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-chloropropyltriethoxy ... silane, n-butyltriethoxysilane, isobutyltrimethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, hexylmethyldimethoxysilane, hexylmethyldiethoxysilane, cyclohexylmethyldiethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, phenyltriethoxysilane, trifluoropropyltrimethoxysilane, tridecafluorooctyltrimethoxysilane, or hydrolysis products thereof.

[0066] Examples of organopolysiloxanes include dimethylpolysiloxane, methylhydrogenpolysiloxane, methylmethoxypolysiloxane, methylphenylpolysiloxane, dimethylpolysiloxanediol, dimethylpolysiloxanedihydrogen, side chain or both terminal amino-modified polysiloxane, side chain or both terminal or one terminal epoxy-modified polysiloxane, both terminal or one terminal methacryl-modified polysiloxane, side chain or both terminal carboxyl-modified polysiloxane, side chain or both terminal or one terminal carbino Examples of the polysiloxanes include phenol-modified polysiloxanes at both ends, mercapto-modified polysiloxanes at either side or both ends, polyether-modified polysiloxanes at either side or both ends, alkyl-modified polysiloxanes at either side, methylstyryl-modified polysiloxanes at either side, higher carboxylate-modified polysiloxanes at either side, fluoroalkyl-modified polysiloxanes at either side, alkyl-carbinol-modified polysiloxanes at either side, amino-modified polysiloxanes at either side or both ends, and copolymers thereof.

[0067] Examples of the organosilazane include hexamethylsilazane and hexamethylcyclotrisilazane.

[0068] A method for forming a coating layer on titanium dioxide will now be described.

[0069] A known method can be used to form a coating layer of a metal oxide. For example, when coating with aluminum oxide, an aqueous solution of an aluminum compound is added to an aqueous slurry in which titanium oxide particles are dispersed, and the coating layer can be formed by adjusting the pH to 4 to 9 using an aqueous solution of an acidic or basic compound. Thereafter, filtration, washing, and drying may be performed as necessary. As the acidic oxide used to adjust the pH, inorganic acids such as sulfuric acid and hydrochloric acid, or organic acids such as acetic acid and formic acid can be used. In addition, as the basic compound, known compounds such as sodium hydroxide, potassium hydroxide, and ammonia can be used. The nonvolatile concentration of titanium dioxide particles in the aqueous slurry is preferably 50 to 800 g / l, more preferably 100 to 600 g / l. By setting the nonvolatile concentration to a predetermined value, a coating layer of uniform thickness can be easily obtained.

[0070] Examples of the aluminum compound include sodium aluminate, aluminum sulfate, aluminum nitrate, aluminum chloride, alumina, and hydrous alumina.

[0071] When coating with silicon oxide or zirconium oxide, a coating layer of silicon oxide or aluminum oxide can be formed using a silicon compound or zirconium compound in the same manner as aluminum oxide. When a coating layer is formed with a plurality of metal oxides, the coating layer can be formed with a mixture containing an aluminum compound. The coating layer may be formed by sequentially using each compound, and the order of forming the coating layer is not limited. Among these coating methods, it is more preferable from the viewpoint of dispersibility with resin to form a coating layer such that aluminum oxide is the outermost layer after forming a coating layer of silicon oxide or zirconium oxide. Furthermore, when forming a coating layer of titanium oxide, processes such as dehydration, drying, and pulverization are facilitated, and the yield is further improved. In the present invention, the coating layer formed with inorganic oxide may have three layers, for example, a coating layer of aluminum oxide, a coating layer of silicon oxide, and a coating layer of zirconium oxide.

[0072] Examples of the silicon compound include water-soluble alkali metal silicates such as sodium silicate, etc. Examples of the zirconium compound include zirconium sulfate, zirconium nitrate, zirconium chloride, etc. Examples of the zirconium compound include zirconium sulfate, zirconium nitrate, and zirconium chloride.

[0073] The method for forming the organic coating layer is preferably (1) a method in which titanium dioxide having a first coating layer is subjected to solid-liquid separation from an aqueous slurry, dried, and then contacted with the organosilicon compound in a gas phase to form a coating layer (hereinafter referred to as a gas phase method), or (2) a method in which titanium oxide is contacted with the organosilicon compound in an aqueous slurry to form a coating layer (hereinafter referred to as a liquid phase method).

[0074] The gas phase method can be carried out by stirring and mixing titanium oxide and the organosilicon compound using, for example, a dry grinding machine such as a fluid energy grinder or an impact grinder, or a high-speed mixer such as a Henschel mixer or a super mixer.

[0075] The liquid phase method can be carried out by forming the first coating layer, and then subsequently adding the organosilicon compound to the aqueous slurry, followed by stirring and mixing.

[0076] The shrinkable substrate of the present invention may contain additives such as pigments, antistatic agents, ultraviolet absorbers, antioxidants, and antiblocking agents, or the substrate surface may be corona-treated or low-temperature plasma-treated. The additives may be used alone or in combination.

[0077] As the pigment, any of the CI pigments described in the Color Index that can be generally used for plastic kneading can be used. For example, color pigments such as titanium oxide, red iron oxide, Prussian blue, ultramarine blue, carbon black, graphite, and extender pigments such as calcium carbonate, kaolin, clay, barium sulfate, aluminum hydroxide, and talc can be used. Furthermore, as the organic pigment, soluble azo pigments, insoluble azo pigments, azo chelate pigments, condensed azo pigments, copper phthalocyanine pigments, condensed polycyclic pigments, and the like can be used. The content of these pigments in the shrinkable substrate can be 0.5 to 50% by weight. In particular, from the viewpoint of hiding power and film-forming properties, it is preferable to use 7 to 25% by weight of titanium oxide.

[0078] Antistatic agents are used to prevent dust from adhering to shrinkable substrates. Examples include higher fatty acid esters, polyhydric alcohol fatty acid esters, anionic surfactants, cationic surfactants, and nonionic surfactants. Specific examples include alkylsulfonates, alkylbenzenesulfonates, N-bis-2-hydroxyethyl-alkylamines, fatty acid choline esters, polyoxyethylene alkyl ethers, phosphoric esters and their salts, fatty acid monoglycerides, and fatty acid sorbitan partial esters. The antistatic agent can be used in an amount of 0.1 to 1% by mass in the shrinkable substrate.

[0079] The ultraviolet absorber is used to improve weather resistance. For example, benzophenone compounds, benzotriazole compounds, triazine compounds, salicylic acid ester compounds, etc. are preferable. Specifically, for example, 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-t-butylphenyl)benzotriazole, 2-(2-hydroxy-3,5-dimethylphenyl)benzotriazole, 2-(2-methyl-4-hydroxyphenyl)benzotriazole, 2-(2-hydroxy-3-methyl-5-t-butylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-t-butylphenyl)benzotriazole, 2-(2-hydroxy-3, 5-dimethylphenyl)-5-methoxybenzotriazole, 2-(2-hydroxy-3-t-butyl-5-methylphenyl)-5-chlorobenzotriazole, 2-(2-hydroxy-5-t-butylphenyl)-5-chlorobenzotriazole, 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]-5-(octyloxy)phenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-(hexyloxy)phenol, etc. Among these, benzotriazole-based compounds and triazine-based compounds are preferred from the viewpoint of heat resistance. The ultraviolet absorber can be used in an amount of 0.01 to 1% by mass in the shrinkable substrate.

[0080] The antioxidant is used to suppress the decomposition of the resin in a high-temperature atmosphere. For example, monophenol compounds, bisphenol compounds, polymeric phenol compounds, phosphorus compounds, sulfur compounds, etc. are preferable. Specific examples include 2,6-di-tert-butyl-p-cresol, butylated hydroxyanisole, 2,6-di-tert-butyl-4-ethylphenol, 2,2'-methylene-bis-(4-methyl-6-tert-butylphenol), 2,2'-methylene-bis-(4-ethyl-6-tert-butylphenol), 4,4'-thiobis-(3-methyl-6-tert-butylphenol), 4,4'-butylidene-bis-(3-methyl-6-tert-butylphenol). , 3,9-bis[{1,1-dimethyl-2-{β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy}ethyl}2,4,8,10-tetraoxaspiro]5,5-undecane, 1,1,3-tris-(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tetrakis-{methylene-3-(3',5'-di tert-Butyl-4'-hydroxyphenyl)propionate}methane, bis{(3,3'-bis-4'-hydroxy-3'-tert-butylphenyl)butyric acid}glycol ester, dilauryl thiodipropionate, dimyristyl thiodipropionate, distearyl thiopropionate, triphenyl phosphite, diphenyl isodecyl phosphite, phenyl diisodecyl phosphite, 4,4'-butylidene-bis-(3-methyl-6-tert-butyl phenyl-di-tridecyl)phosphite, cyclic neopentanetetraylbis(octadecylphosphite), trisdiphenylphosphite, diisodecylpentaerythritol diphosphite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(3,5-di-tert-butyl-4-hydroxybenzyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-decyloxy-9,Examples of the phosphaphenanthrene include 10-dihydro-9-oxa-10-phosphaphenanthrene, cyclic neopentanetetraylbis(2,4-di-tert-butylphenyl)phosphite, cyclic neopentanetetraylbis(2,6-di-tert-methylphenyl)phosphite, and 2,2-methylenebis(4,6-tert-butylphenyl)octylphosphite. The antioxidant can be used at 0.01 to 0.5% by mass in the shrinkable base material.

[0081] Antiblocking agents are used to reduce friction with a container when wrapping the shrink film around the container, making it easier to attach the film to the container. Specific examples of antiblocking agents include organic beads such as acrylic beads, silicon beads, and styrene beads, and inorganic substances such as silica and aluminosilicate. The antiblocking agent can be used in an amount of 0.01 to 1% by mass in the shrinkable substrate.

[0082] <Shrink film> The shrink film of the present invention is formed by printing a printing ink layer and an overcoat agent on a shrinkable substrate in this order. As described above, it is preferable to use a monolayer film of a polyester resin or a styrene resin as the shrinkable substrate from the viewpoint of shrinkability.

[0083] The shrink film thus obtained can be widely used as a container and packaging material for medicines, food, toiletries, etc.

[0084] <Average transmittance from 400 to 700 nm> The average transmittance in the present invention refers to a value calculated as an average value of the transmittance at wavelengths of 400 to 700 nm using a spectrophotometer, such as UV-VIS-NIR SPECTROPHOTOMETER UV3150 manufactured by Shimadzu Science Corporation.

[0085] <60° gloss> The glossiness in the present invention refers to a value measured according to JIS Z 8741, and is a value measured at an incidence angle of 60°. The glossiness can be measured, for example, using a Micro-TRI-glossmeter manufactured by BYK-Gardner under measurement conditions of an incidence angle of 60° and a receiving angle of 60°. EXAMPLES

[0086] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the present invention, parts and % represent parts by mass and % by mass unless otherwise noted.

[0087] (Molecular weight and molecular weight distribution) The weight average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) were measured by GPC (gel permeation chromatography) and calculated as molecular weights using polystyrene as a standard substance. The measurement conditions are shown below. GPC equipment: Showa Denko Shodex GPC-104 Columns: The following columns were used in series connection: Showa Denko Shodex LF-404 x 2 Showa Denko Shodex LF-G Detector: RI (differential refractometer) Measurement conditions: Column temperature 40℃ Eluent: Tetrahydrofuran Flow rate: 0.3mL / min

[0088] (Hydroxyl value) In the following, the hydroxyl value was measured according to the method described in JIS K0070 (1992).

[0089] (glass transition temperature) The glass transition temperature (Tg) was measured using a DSC-TA60 (differential scanning calorimeter) manufactured by Shimadzu Corporation. Approximately 2 mg of a sample obtained by drying the binder resin composition was weighed on an aluminum pan, and the aluminum pan was set in a DSC measurement holder. The endothermic peak of the chart obtained under the temperature increase condition of 5°C / min was read. The peak temperature at this time was taken as the glass transition temperature.

[0090] <Synthesis of polyurethane resin for printing ink> [Synthesis Example 1] (Preparation of urethane resin PU1 solution) 150 parts of polyester polyol (PMPA) with a number average molecular weight of 1,000 obtained by the reaction of adipic acid and 3-methyl-1,5-pentanediol, 50 parts of polypropylene glycol (PPG700) with a number average molecular weight of 700, 103.4 parts of isophorone diisocyanate (IPDI), and 75.8 parts of ethyl acetate (EA) were reacted under a nitrogen stream at 80 ° C for 4 hours to obtain a resin solution of terminal isocyanate urethane prepolymer. Next, 44.6 parts of isophorone diamine (IPDA) and 736.2 parts of a mixed solvent of EA / isopropanol (IPA) = 50 / 50 (mass ratio) were mixed, and the above-mentioned resin solution of terminal isocyanate urethane prepolymer was gradually added at 40 ° C, and then reacted at 80 ° C for 1 hour to obtain a polyurethane resin solution PU1 with a solid content of 30%, an amine value of 9.5 mg KOH / g, a hydroxyl value of 0 mg KOH / g, and a weight average molecular weight of 50,000.

[0091] <Adjustment of resin for overcoat agent> [Synthesis Example 2] (Preparation of Polyester Resin A Solution) 258.7 parts of phthalic anhydride, 86.1 parts of coconut oil fatty acid, 86.1 parts of castor oil, and 291.2 parts of trimethylolpropane were charged into a reactor, and gradually heated to 160-240°C while stirring under a nitrogen stream to carry out an esterification reaction. The reaction was carried out at 240°C for more than 1 hour, and when the acid value became 15 or less, the reactor was gradually depressurized to 1-2 Torr. When the predetermined viscosity was reached, the reaction was adjusted with ethyl acetate (EA) so that the solid content was 73% and then removed. The weight average molecular weight of the obtained polyester resin A was 3,300 as a result of GPC measurement, and the glass transition temperature was 53°C as a result of DSC measurement. The hydroxyl value was 109.0 mgKOH / g, and the acid value was 0.2 mgKOH / g. The polyester resin A contains 55% by mass of structural units derived from dibasic acid and polyhydric alcohol as a whole polyester resin A.

[0092] [Synthesis Example 3] (Preparation of Polyester Resin B Solution) 312.5 parts of terephthalic acid, 312.5 parts of isophthalic acid, 140.1 parts of ethylene glycol, and 234.9 parts of neopentyl glycol were charged into a reactor, and the mixture was gradually heated to 160-240°C while stirring under a nitrogen stream to carry out an esterification reaction. The reaction was continued for 1 hour or more at 240°C, and when the acid value became 15 or less, the reactor was gradually depressurized to 1-2 Torr. When the predetermined viscosity was reached, the reaction was stopped and the mixture was taken out. The weight average molecular weight of the obtained polyester resin B was 7,000 as a result of GPC measurement, and the glass transition temperature was 53°C as a result of DSC measurement. The hydroxyl value was 37.4 mgKOH / g, and the acid value was 0.2 mgKOH / g. The polyester resin B contains 100% by mass of the constitutional units derived from dibasic acid and polyhydric alcohol.

[0093] [Synthesis Example 4] (Preparation of Polyester Resin C Solution) 289.8 parts of terephthalic acid, 260.8 parts of isophthalic acid, 35.3 parts of sebacic acid, 90.9 parts of ethylene glycol, 209.1 parts of neopentyl glycol, and 114.1 parts of butyl ethyl propanediol were charged into a reactor, and the mixture was gradually heated to 160-240°C while stirring under a nitrogen stream to carry out an esterification reaction. The reaction was carried out at 240°C for more than 1 hour, and when the acid value became 15 or less, the reactor was gradually depressurized to 1-2 Torr. When the predetermined viscosity was reached, the reaction was stopped and the mixture was taken out. The weight average molecular weight of the obtained polyester resin C was 26,000 as a result of GPC measurement, and the glass transition temperature was 48°C as a result of DSC measurement. The hydroxyl value was 10.2 mgKOH / g, and the acid value was 0.2 mgKOH / g. The polyester resin C contains 100% by mass of the constitutional units derived from dibasic acid and polyhydric alcohol as a whole polyester resin C.

[0094] [Synthesis Example 5] (Preparation of Polyester Resin D Solution) 286.2 parts of terephthalic acid, 200.3 parts of isophthalic acid, 104.5 parts of sebacic acid, 89.8 parts of ethylene glycol, 206.5 parts of neopentyl glycol, and 112.7 parts of butyl ethyl propanediol were charged into a reactor, and the mixture was gradually heated to 160-240°C while stirring under a nitrogen stream to carry out an esterification reaction. The reaction was carried out at 240°C for 1 hour or more, and when the acid value became 15 or less, the pressure in the reactor was gradually reduced to 1-2 Torr. When the predetermined viscosity was reached, the reaction was stopped and the mixture was taken out. The weight average molecular weight of the obtained polyester resin D was 23,000 as a result of GPC measurement, and the glass transition temperature was 30°C as a result of DSC measurement. The hydroxyl value was 10.2 mgKOH / g, and the acid value was 0.2 mgKOH / g. The polyester resin D contains 100% by mass of structural units derived from dibasic acids and polyhydric alcohols as a whole polyester resin D.

[0095] [Preparation Example 6] (Polyester Resin E) P-5010 (a polyester resin which is a copolymer of 3-methyl-1,5-pentanediol and adipic acid, with a number average molecular weight of 5,000 and a hydroxyl value of 23 mgKOH / g) manufactured by Kuraray Polyol Co., Ltd. Polyester resin E contains 100% by mass of structural units derived from a dibasic acid and a polyhydric alcohol.

[0096] [Synthesis Example 7] (Polyester Resin F) 100 parts of DL-lactide, 100 parts of L-lactide, 0.2 parts of sodium isethionate, and 0.5 parts of tin octoate as a ring-opening polymerization catalyst were charged into a four-neck flask and heated at 180°C for 2 hours under a nitrogen atmosphere to cause ring-opening polymerization, yielding Polyester Resin F with a solid content of 100%, a hydroxyl value of 2.5 mgKOH / g, and a weight average molecular weight of 59,000. Polyester Resin F does not contain any constituent units derived from a dibasic acid and a polyhydric alcohol.

[0097] [Synthesis Example 8] (Preparation of Polyester Resin G Solution) 190.1 parts of phthalic anhydride, 207.9 parts of castor oil, 38.6 parts of ethylene glycol, 63.4 parts of pentaerythritol, and 500.0 parts of ethyl acetate were charged into a reactor, and the mixture was gradually heated to 160-240°C while stirring under a nitrogen stream to carry out an esterification reaction. The reaction was carried out at 195°C for 1 hour or more, and when the acid value became 15 or less, the reactor was gradually depressurized to 1-2 Torr. When a predetermined viscosity was reached, the mixture was adjusted to 50% solids with ethyl acetate (EA) and taken out to obtain polyester resin G. Polyester resin G has 6% by mass of an aromatic ring structure and contains 100% by mass of structural units derived from dibasic acids and polyhydric alcohols as a whole polyester resin G.

[0098] [Synthesis Example 9] (Preparation of acrylic resin solution) In a reactor equipped with a reflux condenser, a dropping funnel, a gas inlet tube, a stirrer, and a thermometer, 40 parts of butyl methacrylate, 10 parts of methacrylic acid, 50 parts of 2-hydroxyethyl methacrylate, 40 parts of ethyl acetate (EA), and 40 parts of isopropyl alcohol (IPA) were charged while introducing nitrogen gas, and the temperature was raised to 90°C. 1 part of azobisisobutyronitrile (AIBN) and 15 parts of EA were added and a polymerization reaction was carried out for 4 hours, and further 0.1 part of AIBN and 3 parts of EA were added and reacted for 2 hours to obtain an acrylic resin solution. IPA was added to the resulting acrylic resin solution to adjust the solid content, yielding an acrylic resin solution with a solid content concentration of 30%, a weight average molecular weight of 30,000, an acid value of 65 mgKOH / g, and a hydroxyl value of 216 mgKOH / g.

[0099] [Synthesis Example 10] (Preparation of urethane resin PU2 solution) 200 parts of PPG700, 127 parts of IPDI, and 81.8 parts of EA were reacted under a nitrogen stream at 80°C for 4 hours to obtain a resin solution of a terminal isocyanate urethane prepolymer. Next, 49.5 parts of IPDA, 3 parts of 2-ethanolamine, and 803.9 parts of a mixed solvent of EA / IPA=50 / 50 (mass ratio) were mixed, to which the obtained resin solution of the terminal isocyanate urethane prepolymer was gradually added at 40°C, and then reacted at 80°C for 1 hour to obtain a polyurethane resin solution PU2 with a solid content of 30%, an amine value of 3.5mgKOH / g, a hydroxyl value of 7.3mgKOH / g, and a weight average molecular weight of 40,000.

[0100] [Preparation Example 11] (Preparation of cellulose resin solution) 30 parts of nitrocellulose (DHX3-5, Nobel NC.CO., Ltd.) was mixed and dissolved in 49 parts of ethyl acetate and 21 parts of isopropyl alcohol to obtain a nitrocellulose resin solution with a solid content of 30%. The pyranose ring structure is 32% by mass.

[0101] [Preparation Example 12] (Preparation of vinyl chloride copolymer resin solution) 30 parts of vinyl chloride copolymer resin (Solvine TAO, manufactured by Nissin Chemical Industry Co., Ltd.) was mixed and dissolved in 70 parts of ethyl acetate to obtain a vinyl chloride copolymer resin solution having a solid content of 30%.

[0102] <Printing ink manufacturing> [Production Example 1] (Production of black printing ink R1) As the binder resin, 32 parts of urethane resin solution PU1 (solid content 30%), 3 parts of vinyl chloride-vinyl acetate copolymer resin (manufactured by Nisshin Chemical Co., Ltd., Solvine TAO, solid content 30%, EA solution), 1.0 part of chlorinated polypropylene resin (manufactured by Nippon Paper Industries Co., Ltd., 370M, chlorine content 30%, solid content 50%), 2 parts of polyethylene wax (manufactured by Mitsui Chemicals, Inc., Hiwax 320P, average particle size 2.5 μm, solid content 40% dispersion), 10 parts of black pigment (carbon black), and 52 parts of a solution of methyl ethyl ketone (MEK) / n-propyl acetate (NPAC) / IPA = 40 / 40 / 20 (mass ratio) were mixed and dispersed for 15 minutes with an Eiger mill to obtain printing ink R1.

[0103] [Production Example 2] (Production of white printing ink R2) As the binder resin, 25 parts of urethane resin solution PU1 (solid content 30%), 5 parts of vinyl chloride-vinyl acetate copolymer resin (manufactured by Nisshin Chemical Co., Ltd., Solvine TAO, solid content 30%, EA solution), 1.0 part of chlorinated polypropylene resin (manufactured by Nippon Paper Industries Co., Ltd., 370M, chlorine content 30%, solid content 50%), 2 parts of polyethylene wax (manufactured by Mitsui Chemicals, Inc., Hiwax 320P, average particle size 2.5 μm, solid content 40% dispersion), 30 parts of white pigment (manufactured by Teika Co., Ltd., Titanix JR-808, titanium oxide), and 37 parts of a solution of methyl ethyl ketone (MEK) / n-propyl acetate (NPAC) / IPA = 40 / 40 / 20 (mass ratio) were mixed and dispersed for 15 minutes with an Eiger mill to obtain printing ink R2.

[0104] [Table 1]

[0105] <Preparation of overcoat agent> [OC Production Example 1] (Preparation of Overcoat Agent S1) 7.8 parts of polyester resin A solution, 28.6 parts of cellulose resin solution (cellulose resin), 20.8 parts of XDI-TMP adduct (trimethylolpropane adduct of xylylene diisocyanate, Mitsui Chemicals, Takenate D-110N, solid content 33%), 0.1 parts of TEGO450 (EVONIC, TEGO Glide 450, polyether siloxane copolymer), and 42.7 parts of EA were mixed and stirred for 30 minutes with a disperser to obtain an overcoat agent S1 with a solid content of 30%. Polyester resin A contains 77% by mass of structural units derived from dibasic acid and polyhydric alcohol as a whole polyester resin A.

[0106] [OC Production Examples 2 to 22, Comparative OC Production Examples 1 to 7] (Preparation of Overcoat Agents S2 to S22, SS1 to SS7) Overcoat agents S2 to S22 and SS1 to SS7 were obtained in the same manner as in OC Production Example 1, except that the raw materials and blending ratios shown in Tables 2 and 3 were used.

[0107] [Table 2]

[0108] [Table 3]

[0109] The abbreviations and details of the raw materials in Tables 2 and 3 are shown below. XDI (xylylene diisocyanate)-TMP (trimethylolpropane) adduct: Mitsui Chemicals, Takenate D-110N, solids content 33%, NCO content 12% TDI (toluene diisocyanate)-TMP adduct: Sumika Bayer Urethane Co., Ltd., Desmodur L75(C), solid content 75%, NCO content 13% HDI (hexamethylene diisocyanate)-TMP adduct: Asahi Kasei Chemicals Corporation, Duranate P301-75E, solids content 75%, NCO content 13% HDI-biuret, Asahi Kasei Chemicals Corporation, Duranate 24A-100, solids content 100%, NCO content 23.5% IPDI: Isophorone diisocyanate

[0110] The ester bond concentrations of the polyester resins synthesized and used above were as follows. Polyester resin A: ester bond concentration 5.6 mmol / g Polyester resin B: ester bond concentration 9.4mmol / g Polyester resin C: ester bond concentration 8.7mmol / g Polyester resin D: ester bond concentration 8.5mmol / g Polyester resin E: Ester bond concentration 8.8mmol / g Polyester resin F: Ester bond concentration 13.9 mmol / g Polyester resin G: ester bond concentration 7.1mmol / g

[0111] <Preparation of shrinkable substrates Shrinkable substrates 1-17> The shrinkable substrate was prepared by molding a 50 μm thick sheet at 290°C using a T-die extruder using a masterbatch containing 50% by mass of titanium oxide having the average particle size and purity shown in Table 4 and polyethylene terephthalate. The masterbatch was prepared by molding at 280°C using a twin-screw extruder using the same polyethylene terephthalate resin as that used for sheet molding.

[0112] [Table 4]

[0113] [Example 1] <Preparation of shrink film using printing ink R2 and overcoat agent S1> Printing ink R2 and overcoat agent S1 were each diluted with a mixed solvent of EA / IPA (mass ratio 70 / 30) to a viscosity of 15 seconds in a Zahn cup #3 (manufactured by Rigo Co., Ltd.) at 25° C. The diluted printing ink R2 was applied to the prepared polyester film having a thickness of 50 μm using a gravure printing machine equipped with a gravure plate having a plate depth of 35 μm under conditions of a printing speed of 40 m / min and a dryer temperature of 50° C., to obtain a printed film. Next, the diluted overcoat agent S1 was applied to the printed surface of the printed film prepared above using a gravure printing machine equipped with a gravure plate with a plate depth of 35 μm at a printing speed of 40 m / min and a dryer temperature of 50°C to obtain a shrink film having a composition of shrinkable substrate / printed layer / transparent protective layer.

[0114] [Examples 2 to 39] For each of the printing inks and overcoat agents obtained in the above manufacturing examples, examples, or comparative examples, shrink films having the same printing configuration were each produced in the same manner as for producing the above shrink films, except that the printing inks and overcoat agents shown in Table 5 were used.

[0115] <Characteristics evaluation> The overcoat agents obtained in the above Examples and Comparative Examples and their printed matter were subjected to the following evaluations. The evaluation results are shown in Table 5.

[0116] <Gloss> The gloss value was measured at an incident angle of 60° and a receiving angle of 60° using a Micro-TRI-glossmeter manufactured by BYK-Gardner from the transparent protective layer side of the shrink films produced in the above Examples and Comparative Examples. The evaluation criteria are shown below. A (Excellent): Gloss value is 22 or higher. B (Acceptable): Gloss value is 13 or more and less than 22. C (unacceptable): Gloss value is less than 13. A and B are within the range where there are no practical problems.

[0117] <Adhesion (tape adhesion resistance)> The shrink films produced in the above Examples and Comparative Examples were evaluated for the degree of peeling of the printed layer or transparent protective layer when cellophane tape (12 mm wide) manufactured by Nichiban Co., Ltd. was applied onto the transparent protective layer and then rapidly peeled off. The evaluation criteria are shown below. A (Excellent): The printing layer or transparent protective layer does not peel off at all. B (Acceptable): Less than 50% of the printed layer or transparent protective layer peels off. C (Fail): 50% or more of the printed layer or transparent protective layer peels off. A and B are within the range where there are no practical problems.

[0118] <Heat resistance> The shrink films produced in the above examples and comparative examples were each cut to a size of 3 cm x 13 cm, and the glossy side of an aluminum foil (thickness 30 μm) cut to the same size was placed on the printed side of the printed matter. The aluminum foil was pressed with a pressure of 2 x 9.8 N / cm2 at 120°C for 1 second using a Sentinel heat sealer, and the degree of peeling of the printed layer or transparent protective layer when the aluminum foil was peeled off was visually judged. The evaluation criteria are shown below. A (Excellent): No peeling at all at a seal bar temperature of 160°C. B (Acceptable): Does not peel off at a seal bar temperature of 120°C, but peels off at 160°C. C (Not acceptable): Peels off at a seal bar temperature of 120°C. A and B are within the range where there are no practical problems.

[0119] [Table 5]

[0120] <Reference Example 1: Evaluation of only surface-printed matter using printing ink> Each printing ink R3 was diluted with a mixed solvent of EA / IPA (mass ratio 70 / 30) so that the ink would last for 15 seconds at 25° C. in a Zahn cup #3 (manufactured by Rigo Co., Ltd.). The diluted printing ink R3 was applied to the prepared shrinkable polyester film substrate having a thickness of 50 μm using a gravure printing machine equipped with a gravure plate having a plate depth of 35 μm at a printing speed of 40 m / min and a dryer temperature of 50°C to obtain a printed matter A1 with a surface print configuration. The same evaluation as above was carried out on the printed matter A1 with a surface printing configuration. The gloss was C, and the adhesion was A. , heat resistance: C.

[0121] The above evaluation results show that by using the overcoat agent defined in the present invention, in the examples, a shrink film can be obtained that improves the gloss of the transparent protective layer and exhibits even better adhesion and heat resistance. On the other hand, Comparative Example 1 did not contain an isocyanate curing agent, and was inferior in adhesion and heat resistance. Comparative Example 2 contained less than 30% by mass of polyester resin in the entire binder resin, and the gloss and heat resistance were inferior. Comparative Example 3 did not contain a ring structure, and the gloss was inferior. Comparative Example 4 did not contain 50% by mass or more of the constitutional unit derived from dibasic acid and polyhydric alcohol in the entire polyester resin, and the coating film was brittle, and the gloss, adhesion and heat resistance were inferior. Comparative Example 5 did not contain polyester resin, and the heat resistance was inferior. Comparative Example 6 was an acrylic resin binder that did not contain polyester resin, and the heat resistance and adhesion were inferior. Comparative Example 7 did not contain polyester resin, and the gloss and heat resistance were inferior.

Claims

1. A shrink film comprising an overcoat layer (A), a printing layer (B), and a shrinkable substrate (C), The overcoat layer (A) is formed from an overcoat agent containing a binder resin and an isocyanate curing agent, The binder resin contains a polyester resin in an amount of 30% by mass or more of the entire binder resin, The polyester resin contains structural units derived from a polybasic acid and a polyhydric alcohol in an amount of 50 mass% or more of the entire polyester resin, The polyester-based resin is at least one of a polyester resin and an alkyd resin, Either or both of the binder resin and the isocyanate curing agent contain at least one cyclic structure selected from an aromatic ring, an alicyclic ring, and a heterocyclic ring; A shrink film characterized in that the shrinkable substrate (C) contains titanium oxide having an average particle size of 0.15 to 0.35 μm.

2. 2. The shrink film according to claim 1, wherein the content of the cyclic structure is 7 to 50% by mass of the total solid content of the overcoat agent.

3. The shrink film according to claim 1 or 2, wherein the ester bond concentration of the polyester resin is 0.5 mmol / g to 12.0 mmol / g.

4. The shrink film according to any one of claims 1 to 3, wherein the isocyanate curing agent contains an adduct type isocyanate compound and / or a biuret type isocyanate compound.

5. The shrink film according to any one of claims 1 to 4, wherein the binder resin further contains a cellulose-based resin or a vinyl chloride copolymer resin, and the mass ratio of the polyester-based resin to the cellulose-based resin or the vinyl chloride copolymer resin is 90:10 to 30:

70.

6. 6. The shrink film according to claim 1, wherein the printed layer (B) includes a layer in which either or both of a white layer and a black layer are solid printed.

7. The shrink film according to any one of claims 1 to 6, wherein the shrink film after application of the printing layer and the overcoat layer has an average transmittance of 15% or less at 400 to 700 nm and a 60° gloss of 20 or more.

Citation Information

Patent Citations

  • JP1981167382U

  • Device for firing discharge lamp

    JP1983028196A

  • Over-printing varnish composition

    JP2003147265A

  • Shrink label and labeled container

    JP2008201463A

  • Cylindrical shrink label and method for producing the same

    JP2015013443A